Emergency Remote Teaching (ERT) Practices from the Perspective of Classroom Teachers Teaching in Disadvantaged Suburban Primary School - Ozgul MUTLUER; Bunyamin BAVLI (Anı Publishing, 2022)
The current study aims to determine how emergency remote teaching (ERT) practices were conducted in a disadvantaged suburban public primary school during the COVID -19 pandemic. For this purpose, a disadvantaged suburban public primary school in the Marmara region, Turkey, was selected as a case and an instrumental case study design was chosen for the study. For data collection, in-depth interviews were conducted using a semi-structured interview form with 10 classroom teachers. In addition, natural observations were conducted by one of the researchers who is also a teacher in the same school. As a result of the thematic analysis, two main themes were identified: "disadvantage experienced by students" and "the consequences of disadvantage." The disadvantage experienced by the students has two different dimensions, social and economic. It was found that these disadvantages lead to different effects on students and teachers. The results of the study show that students face economic disadvantages in purchasing the imperative learning materials to participate in the online course. Parents do not prioritize these materials due to low awareness. Socio-economic disadvantages lead to a digital divide and inequality of opportunity in education.It is clear that school closures will create even greater challenges for disadvantaged students in the future.s. In terms of teachers, these disadvantageous situations cause instructional difficulties such as challenges in planning the teaching process, neglecting the program, effective assessment; and individual difficulties such as anxiety and sadness.